2009
DOI: 10.1002/nur.20353
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of physical activity in low income college students

Abstract: The importance of physical activity as a health promoting behavior has been well documented. We examined the relationship of social support, self-efficacy, and commitment to a plan of physical activity on physical activity behaviors in a sample of low income college students. Those with higher levels of social support, self-efficacy, and commitment to a plan of physical activity reported more physical activity behaviors. Commitment to a plan of physical activity mediated the relationships of social support and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
3
20
0
1
Order By: Relevance
“…Furthermore, Maglione & Hayman [11] reported a positive correlation between social support, self-efficiency and a commitment to engage in physical activity among under-privileged college students, as they demonstrated that those with high levels of social support, self efficiency and a commitment to plan for physical activity reported higher physical activity performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Maglione & Hayman [11] reported a positive correlation between social support, self-efficiency and a commitment to engage in physical activity among under-privileged college students, as they demonstrated that those with high levels of social support, self efficiency and a commitment to plan for physical activity reported higher physical activity performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies carried out with university students from different countries have shown divergences as regards the perceived barriers [14][15][16] . The main limiting factors were lack of energy, lack of motivation and lack of self-confidence (internal or personal barriers) 14 and the social support from family members and friends (relative outside barriers) 14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies carried out with university students from different countries have shown divergences as regards the perceived barriers [14][15][16] . The main limiting factors were lack of energy, lack of motivation and lack of self-confidence (internal or personal barriers) 14 and the social support from family members and friends (relative outside barriers) 14,16 . It is believed that the differences of the present study, when compared to the researches carried out with Turkish 14 and Spanish 15 university students may be related to the characteristics of each region, mainly as regards the socio-cultural and economic context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular participation in physical activity is a health promoting behaviour with substantive physiological and psychological health benefits for people of all ages (Maglione & Hayman, 2009;Romaguera et al, 2011). While young adulthood is characterized by the development of individuals' lifestyles, it is also associated with a decline in physical activity levels (Fountaine, Liguori, Mozumdar, & Schuna, 2011;Keating, Guan, Pinero, & Bridges, 2005).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%